Economic strategies of the Herdez Group - Lázaro-Pérez, Deysi E. (2023)
The Mexican processed food industry has a total of 204, 623 economic units. This study defines the evolution of Grupo Herdez, leader in the sector, it has positioned itself as one of the most outstanding groups in Mexico with a presence in the United States. Objective: Analyze the competitive strategies used by Grupo Herdez in order to consolidate itself in the food industry as the most important group and expand internationally. Material and Method: The historical, analytical and descriptive methods were used. Secondary sources were consulted: literary review, website, reports and annual reports of the Herdez Group. Results: The period studied from 2000 to 2022 marks a sustained growth of Grupo Herdez, pointing out its infrastructure strategies, store openings, investment, divestment, alliances, acquisitions, financing, product diversification and technology, allowing it to position itself as a highly recognized Mexican company. and with presence in the national and international market. Conclusion: Based on the success of its strategies, Grupo Herdez has consolidated itself efficiently in the processed and frozen food market, to become one of the most profitable economic groups in the international market.